Cambodia Economic Update, April 2017 : Staying Competitive through Improving Productivity - World Bank Group (World Bank, Phnom Penh, 2017)
Growth remained strong at 6.9 percent in 2016, after 7.0 percent in 2015. Cambodia's economic activity continues to expand at a robust pace. Construction remained one of the main drivers of growth. Garment exports eased slightly as the country’s external competitiveness was eroded by US dollar appreciation, rising labor costs and increasing competition from other regional low-wage countries. Better weather conditions last year resulted in increased agricultural production, although agricultural commodity prices remain depressed. Real growth is projected to remain strong, expanding at 6.9 percent in 2017 and 2018, partly underpinned by government spending. Downside risks to this outlook include the fallout from further rises in US interest rates, a slower-than-expected economic recovery in Europe, and uncertainties over global trade. Poverty reduction is expected to continue over the next few years, driven mainly by the garment, construction and services sectors, together with increases in remittances.